ACCESS TO JUSTICE UNDER ARTICLE 6 OF THE EUROPEAN CONVENTION ON HUMAN RIGHTS - Selegea, Mihai (Boletim Científico Escola Superior do Ministério Público da União, 2002)
Sumary: 1. Introduction. 2. Field of application of the right. 3. Content of the right of access to court. 4. Conclusion